2021
DOI: 10.1111/jems.12462
|View full text |Cite
|
Sign up to set email alerts
|

Does female labor scarcity encourage innovation? Evidence from China's gender imbalance

Abstract: This paper studies how the scarcity of different types of workers in a region shapes firm innovation across industries, using the unbalanced regional sex ratios in China as a source of identification strategy. The empirical resultsshow that the shortage of female workers has spurred firms in femaleintensive industries to innovate more, particularly in industries with low substitution between female and male workers, consistent with the price effect of the directed technical change theory. In male-intensive ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
3

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 47 publications
0
3
0
3
Order By: Relevance
“…Os achados corroboram, ainda, uma contestação do discurso hegemônico tão presente em sistemas políticos abertos de economia neoliberal, qual seja: a "[...] inovação representa uma solução para o progresso econômico e social da sociedade"; ou, ainda: "[...] o progresso econômico induz necessariamente ao progresso social". Tal discurso se provaria incoerente diante de economias de regimes políticos fechados que, apesar de economicamente avançadas, ainda possuem uma cultura restritiva Outra questão revelada pelos achados se refere à desigualdade estrutural de gênero no acesso a programas voltados à inovação, uma vez que, no melhor dos cenários, nessas mesmas sociedades as mulheres de negócios são constantemente associadas mais à inovação intraorganizacional e menos à inovação organizacional (Chen et al, 2021;Filculescu, 2016). Esse contexto também se verifica na dimensão contemplada pelo GII, por meio do indicador females employed with advanced degrees, que apresenta a força de trabalho feminina com qualificação profissional tal qual um ativo das empresas inovadoras.…”
Section: Gráfico 3 Visualização Gráfica Do Modelo De Regressão Linear...unclassified
See 2 more Smart Citations
“…Os achados corroboram, ainda, uma contestação do discurso hegemônico tão presente em sistemas políticos abertos de economia neoliberal, qual seja: a "[...] inovação representa uma solução para o progresso econômico e social da sociedade"; ou, ainda: "[...] o progresso econômico induz necessariamente ao progresso social". Tal discurso se provaria incoerente diante de economias de regimes políticos fechados que, apesar de economicamente avançadas, ainda possuem uma cultura restritiva Outra questão revelada pelos achados se refere à desigualdade estrutural de gênero no acesso a programas voltados à inovação, uma vez que, no melhor dos cenários, nessas mesmas sociedades as mulheres de negócios são constantemente associadas mais à inovação intraorganizacional e menos à inovação organizacional (Chen et al, 2021;Filculescu, 2016). Esse contexto também se verifica na dimensão contemplada pelo GII, por meio do indicador females employed with advanced degrees, que apresenta a força de trabalho feminina com qualificação profissional tal qual um ativo das empresas inovadoras.…”
Section: Gráfico 3 Visualização Gráfica Do Modelo De Regressão Linear...unclassified
“…Esse contexto também se verifica na dimensão contemplada pelo GII, por meio do indicador females employed with advanced degrees, que apresenta a força de trabalho feminina com qualificação profissional tal qual um ativo das empresas inovadoras. Isso se torna um agravante em regiões de países em desenvolvimento, a exemplo do Brasil e da China, onde a distribuição desigual entre mão de obra feminina e masculina também pode influenciar o nível de inovação que as indústrias conseguem atingir, sem, no entanto, gerar qualquer contraprestação social para que uma maior inserção das mulheres no mercado de trabalho técnico resulte em melhora na qualidade de vida desse público ou de suas famílias, conforme bem ilustrou o estudo de Chen et al (2021). Tal estudo demonstrou uma tendência a uma maior inovação em indústrias com o uso intensivo de força de trabalho feminina em locais da China onde não havia um contingente populacional significativo de mão de obra masculina que pudesse substituí-la.…”
Section: Gráfico 3 Visualização Gráfica Do Modelo De Regressão Linear...unclassified
See 1 more Smart Citation
“…Another issue revealed by our findings refers to the structural gender inequality in access to innovation programmes. In the best-case scenario, in these same societies, businesswomen are more constantly associated with intra-organisational innovation and less with organisational innovation (Chen et al, 2021;Filculescu, 2016). This context can also be seen in the dimension covered by the GII, through the "females employed with advanced degrees" indicator, which presents the female workforce with professional qualifications as an asset of innovative companies.…”
Section: Graph 3 Graphical Display Of the Multiple Linear Regression ...mentioning
confidence: 99%
“…This context can also be seen in the dimension covered by the GII, through the "females employed with advanced degrees" indicator, which presents the female workforce with professional qualifications as an asset of innovative companies. This is aggravating in developing countries, such as Brazil and China, where the unequal distribution between female and male labour can also influence the level of innovation that industries can achieve without, however, generating any social return so that greater inclusion of women in the technical labour market results in an improvement to this group's, or their families, quality of life, as the study by Chen et al (2021) illustrates. This study showed a tendency towards greater innovation in female-intensive industries in Chinese regions where there was no significant population contingent of male labour to replace them.…”
Section: Graph 3 Graphical Display Of the Multiple Linear Regression ...mentioning
confidence: 99%